The Pruritic Urticarial Papules and Plaques of Pregnancy (PUPPP): Papula Urtikaria Pruritik dan Plak pada Kehamilan (PUPPP) - Riyan H. Kurniawan; Ugi U. Dimas; Afria Arista (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objective: To report a rare case of pruritic urticarial papules and plaques of pregnancy (PUPPP) in multiparous woman and its literature review.Methods: A case report with literature review.Discussion: This article reports a multigravida woman, presented with aterm pregnancy with sign and symptoms of pruritic urticarial papules and plaques since the first trimester of pregnancy. This case supports the morphological variation of skin lesions in PUPPP, as the patient had lesions other than the characteristic urticarial papules and plaques, with hyperpigmentation skin changes. The management of this case include oral and topical corticosteroids, oral antihistamines and moisturizer is used to relieve pruritus and skin lesions.Conclusion: PUPPP should be included in the differential diagnosis to differentiate this entity from other dermatoses associated with pregnancy, in order to provide appropriate treatment and reassurance.Keywords: papules, plaques, pregnancy, pruritic, urticarial. Abstrak Tujuan: Untuk melaporkan kasus langka mengenai papula urtikaria pruritik dan plak pada kehamilan (PUPPP) perempuan multipara, membahas literatur terkait pada PUPPP.Metode: Laporan kasus dengan telaah literatur.Diskusi : melaporkan kasus perempuan multigravida, datang dalam usia kehamilan cukup bulan dengan tanda dan gejala papula, plak, urtikaria dan pruritus sejak trimester pertama kehamilan. Kasus ini mendukung variasi morfologi lesi kulit pada PUPPP, karena pasien memiliki lesi selain papula dan plak urtikaria yang khas, dengan perubahan kulit hiperpigmentasi. Penatalaksanaan kasus ini meliputi kortikosteroid oral dan topikal, antihistamin oral dan pelembab yang digunakan untuk meredakan pruritus dan lesi kulit.Kesimpulan: PUPPP perlu dimasukkan dalam diagnosis banding untuk membedakan entitas ini dari penyakit kulit lain yang terkait dengan kehamilan, untuk memberikan pengobatan dan pelayanan yang tepat.Kata kunci: kehamilan, , papula, plak, pruritus, urtikaria